Financing Provision and Sharia Compliance in the BSI Griya Hasanah Product with a Musyarakah Mutanaqisah Contract: A Case Study at BSI KCP Cemara Asri - Sijabat, Winda Irmayani; Anggraini, Tuti; Inayah, Nurul (State of Islamic Institute Langsa, 2025)
Ideally, Islamic banking financing with the Musyarakah Mutanaqisah (MMQ) contract in the BSI Griya Hasanah product should comply with Sharia compliance principles, ensuring the absence of riba, gharar, and maysir elements. However, in reality, the implementation of the MMQ contract at BSI KCP Cemara Asri still faces challenges in Sharia compliance, particularly in the profit-sharing mechanism and legal certainty for customers. This study aims to analyze the financing provision in the BSI Griya Hasanah product and assess its Sharia compliance based on practices at BSI KCP Cemara Asri. This article is classified as a qualitative field research study. The methodology used is an empirical legal study explained through descriptive analytical methods. The analysis shows that the provision of Griya Hasanah financing with the Musyarakah Mutanaqisah contract at BSI KCP Cemara Asri complies with Sharia principles and follows the 5C analysis. However, in terms of Sharia compliance, there is a discrepancy with the DSN-MUI fatwa regarding the distribution of asset acquisition costs and losses. The Sharia Supervisory Board states that while the practice is valid in terms of the contract, it violates the provisions of DSN-MUI Fatwa No. 73/DSN-MUI/XI-2008.